2017
DOI: 10.1186/s40562-017-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Coulomb stress triggering hypothesis for three recent megathrust earthquakes

Abstract: We test the static Coulomb stress triggering hypothesis for three recent megathrust earthquakes (the 2004 Sumatra-Andaman earthquake, the 2010 Maule earthquake, and the 2011 Tohoku-Oki earthquake) using focal mechanism solutions for actual earthquakes as receiver faults to calculate Coulomb stress changes. For the 2004 Sumatra-Andaman and 2011 Tohoku-Oki earthquakes, the median values of the Coulomb stress changes for 100 consecutive earthquakes revealed temporal changes from approximately zero before the mega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Additionally, Ishibe et al . 37 showed that the temporal changes in median ΔCFF from 2000 to the middle of 2015. The median values of ΔCFF rapidly increased just after the Tohoku-oki mainshock, after which the median ΔCFF gradually decreased to background levels approximately 3 years after the mainshock.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ishibe et al . 37 showed that the temporal changes in median ΔCFF from 2000 to the middle of 2015. The median values of ΔCFF rapidly increased just after the Tohoku-oki mainshock, after which the median ΔCFF gradually decreased to background levels approximately 3 years after the mainshock.…”
Section: Discussionmentioning
confidence: 99%
“…Although powerful tsunamis from M > 8 earthquakes occur almost annually in the Pacific Ocean (e.g., Synolakis et al 2002;Fritz et al 2012;Suppasri et al 2013;Satake 2014;Heidarzadeh et al 2016a;Shimozono and Sato 2016;Saito 2017;Ishibe et al 2017), such events are less frequent in the Mediterranean Sea. Therefore, analysis of this moderate tsunami contributes toward tsunami assessment and awareness in this enclosed basin and tests the functional performance of TSPs in the NEAMTWS region.…”
Section: Open Accessmentioning
confidence: 99%
“…Ds is the shear stress changes, and Dr is the normal stress change (Ishibe et al 2015(Ishibe et al , 2017Stein et al 1992). The sign of DCFF indicates increase (for positive values) or decrease (for negative values) in Coulomb stress for the neighboring areas imparted by the mainshock.…”
Section: Methodsmentioning
confidence: 99%